1996
DOI: 10.1007/bf02247439
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-like discriminative stimulus effects of the neurosteroid 3α-hydroxy-5α-pregnan-20-one in femaleMacaca fascicularis monkeys

Abstract: The present study was designed to characterize the discriminative stimulus effects of ethanol and the neurosteroid 3 alpha-hydroxy-5 alpha-pregnan-20-one (allopregnanolone) in non-human primates. Female cynomolgus monkeys (Macaca fascicularis) were trained in a two-lever procedure to discriminate 1.0 g/kg ethanol (IG, 30 min pretreatment) from water using food reinforcement. Consistent with previous results in a variety of species, pentobarbital (0.56-17 mg/kg, IG) resulted in a dose-dependent substitution for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 26 publications
8
56
1
Order By: Relevance
“…Consistent with previous reports, pentobarbital (Ator et al, 1993;Grant et al, 1996;Hodge et al, 2001;Shelton and Grant, 2002) and diazepam (Jarbe and McMillan, 1983;Ator et al, 1993;Kostowski and Bienkowski, 1999;Green-Jordan and Grant, 2000;Shelton and Grant, 2002) dose dependently substituted for the stimulus effects of ethanol. MPEP pretreatment did not alter pentobarbital (1-10 mg/kg) substitution for ethanol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous reports, pentobarbital (Ator et al, 1993;Grant et al, 1996;Hodge et al, 2001;Shelton and Grant, 2002) and diazepam (Jarbe and McMillan, 1983;Ator et al, 1993;Kostowski and Bienkowski, 1999;Green-Jordan and Grant, 2000;Shelton and Grant, 2002) dose dependently substituted for the stimulus effects of ethanol. MPEP pretreatment did not alter pentobarbital (1-10 mg/kg) substitution for ethanol.…”
Section: Discussionsupporting
confidence: 91%
“…For example, positive modulators of GABA A receptors, such as barbiturates, benzodiazepines, and neurosteroids, produce ethanollike stimulus effects (Ator et al, 1993;Barry, 1991;Evans and Balster, 1991;Grant et al, 1996Grant et al, , 1997Jarbe and McMillan, 1983;Shelton and Grant, 2002) in multiple species. MGluR5 activity has the potential to influence ethanol discrimination based on evidence that mGluR5 can influence GABA neurotransmission (de Novellis et al, 2003;Hoffpauir and Gleason, 2002;Diaz-Cabiale et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Even though Gabriel et al (2004) found that allopregnanolone did not influence ethanol-induced place preference, other work emphasized a relationship of neurosteroid action to ethanol pharmacology by demonstrating that discrimination for ethanol generalized to neurosteroids (Ator et al, 1993;Bowen et al, 1999;Grant et al, 1996). Additionally, exogenous neurosteroid altered the reinforcement responding for ethanol (Janak et al, 1998) and reinstated previously extinguished responding for ethanol (Nie and Janak, 2003).…”
Section: Neurosteroid Involvement In the Gabamimetic Profile Of Ethanmentioning
confidence: 99%
“…These behavioral effects of ALLO are similar to those exhibited by ethanol, which exerts some of its effects through an interaction with GABA A receptors (for review, see [18]). Furthermore, ALLO is capable of substituting for ethanol's stimulus effects within drug discrimination procedures employing rodents and primates [3,17,19]. This indicates that the complex interoceptive cue elicited by ethanol (see [16]) demonstrates considerable overlap with ALLO.…”
Section: Introductionmentioning
confidence: 99%